1992
DOI: 10.1002/tox.2530070104
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of herbicide phytotoxicity to Selenastrum capricornutum using microplate and flask bioassay procedures

Abstract: Four reference toxicants (Cr6+, Cu2+, Zn2+, phenol) and 9 herbicides (imazamethabenz, 2,4‐dichlorophenoxyacetic acid, picloram, glyphosate, bromoxynil, metolachlor, diquat dibromide, hexazinone, cyanazine) were appraised using both the microplate and flask assay Ninety‐six hour EC50s determined with Selenastrum capricornutum as the indicator species essentially demonstrated good intermethodological data concordance for all chemicals, with the exception of diquat dibromide, whose phytotoxicity in the microplate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…St-Laurent et al [4] found that Selenastrum was sensitive to metolachlor at 55 g/L (EC50), which is comparable to our 96-h EC50 of 84 g/L. St-Laurent et al [4] found that Selenastrum was sensitive to metolachlor at 55 g/L (EC50), which is comparable to our 96-h EC50 of 84 g/L.…”
Section: Discussionsupporting
confidence: 85%
“…St-Laurent et al [4] found that Selenastrum was sensitive to metolachlor at 55 g/L (EC50), which is comparable to our 96-h EC50 of 84 g/L. St-Laurent et al [4] found that Selenastrum was sensitive to metolachlor at 55 g/L (EC50), which is comparable to our 96-h EC50 of 84 g/L.…”
Section: Discussionsupporting
confidence: 85%
“…We used the Algal Growth Inhibition (AGI) test, in which PPCP samples were exposed to algae (Pseudokirchneriella subcapitata (NIES-35)) in a 96-hole microplate following the standard procedure (Blaise et al 1986;St-Laurent et al 1992) with minor modification (Yamashita et al 2006). For exposure of PPCP samples, dilution series (maximum concentration 10 mg/L) was prepared by serial 1:1 dilution with culture medium in 10 steps.…”
Section: Algaementioning
confidence: 99%
“…Efforts to standardize these assays have been made by international organizations (i.e., ISO, US EPA, and OECD) . Despite these efforts, several authors recommend improving gas‐exchange conditions and limiting the assay to the central part of the plate . However, there are no reports on descriptive or statistical validation of the microplate system for kinetic characterization of microalgae cultures.…”
Section: Introductionmentioning
confidence: 99%